ASEAN-5 countries stock market integration : Pre and post Asian 1997 Financial crisis - Huang, David Tiong Ung (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The objective of this paper is to study the relationship of the stock markets in the Association ofSoutheast Asian Nations (ASEAN-5) countries. In other words, it is to access the ASEAN-5 stock market integration or the long run relationship among the markets. The study of the integration is separate to two parts, which is Pre Asian 1997 Financial Crisis and Post Asian 1997 Financial Crisis. The rationale of this study is to determine whether the investor can have more benefit through international portfolio diversification within the region during pre-crisis and post-cris~The empirical results suggest that the five stock markets are only co integrated after crisis but not in pre-crisis. Investor from outside the region can be benefited by the cointegration because the cost of investing is reduced and the liquidity speed is improved. Although the stock markets are integrated, but integration is not fully complete. Therefore, the investor inside the region is still can have the benefit from the international portfolio diversification.